(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2025)
Understanding the internal microtextural heterogeneity of fluvio-aeolian successions can provide valuable insights both on the depositional mechanisms associated with their origin and on their quality as reservoir rocks. Microfacies analysis enables the integration of thin-section textural studies with outcrop-scale observations, which substantially improves our understanding of depositional dynamics across different subenvironments, as well as the interpretation of petrophysical properties distribution. This approach is particularly relevant for reservoirs such as the Avilé Member of the Agrio Formation, as small-scale textural variability has become increasingly important due to the implementation of enhanced recovery techniques in recent years. This unit is characterised by fluvial and aeolian sandstones and constitutes one of the main conventional hydrocarbon reservoirs in the Neuquén Basin. In light of this, the general objective of this work was to compare aeolian and fluvial laminae to improve small-scale textural heterogeneities modelling of the defined facies from mesoscopic analysis. The methodology involved first describing and interpreting the units at the mesoscopic scale, and then characterising the different lamina types at the microscopic scale to define the microfacies. Five distinct lamina types, each representing a specific sedimentary process, were identified in the field within a well-established stratigraphic framework. Their textural petrographic characterisation allowed the definition of five corresponding microfacies —three associated with aeolian deposits and two with fluvial deposits. The results suggest a strong correspondence between textural parameters and the sedimentary process responsible for deposition. The analysis showed both differences among deposits formed by the same transport and depositional agent, and similarities between aeolian and fluvial deposits formed by analogous depositional mechanisms. This suggests that the depositional process may exert greater control on deposit texture than the characteristics of the transport and depositional agent. The study contributes to a more accurate characterisation of small-scale heterogeneities, which is essential for improving facies modelling and reservoir prediction. Overall, the findings highlight the complexity of interpreting microtextural heterogeneity and underscore the value of detailed microfacies analysis as a complement to field studies for improved reservoir characterisation.